Outcome of Stable Patients With Acute Myocardial Infarction and Coronary Artery Bypass Surgery Within 48 Hours: A Single‐Center, Retrospective Experience. Issue 10 (3rd October 2017) - Grothusen, Christina; Friedrich, Christine; Loehr, Johannes; Meinert, Jette; Ohnewald, Eva; Ulbricht, Ulysses; Attmann, Tim; Haneya, Assad; Huenges, Katharina; Freitag‐Wolf, Sandra; Schoettler, Jan; Cremer, Jochen
Abstract : Background: The optimal timing of coronary artery bypass grafting (CABG) in clinically stable patients with acute myocardial infarction who are unsuitable for percutaneous coronary intervention is unclear. We report our experience with early CABG in these patients. Methods and Results: Between January 2001 and May 2015, 766 patients with ST‐segment–elevation myocardial infarction (STEMI, n=305) or non‐STEMI (NSTEMI, n=461) not including cardiogenic shock underwent CABG within 48 hours at our department. STEMI patients were younger than non‐STEMI patients (age 65 years [range: 58–72] versus 70 years [range: 62–75], P <0.001) with a lower EuroSCORE II (4.12 [range: 2.75–5.81] versus 4.58 [range: 2.80–7.74], P =0.009). STEMI patients had undergone preoperative percutaneous coronary intervention more often (20.3% versus 7.8%, P <0.001). Time to surgery was shorter in STEMI compared with non‐STEMI patients (5.0 hours [range: 3.2–8.8] versus 11.7 hours [range: 6.4–22.0], P <0.001). No significant differences concerning arterial graft use (93.8% versus 94.8%, P =0.540) or complete revascularization (87.5% versus 83.4%, P =0.121) were observed. The rate of strokes did not differ between the groups (2.0% versus 3.9%, P =0.134). Thirty‐day mortality was lower in STEMI patients (2.7% versus 6.6% P =0.018), especially when CABG was performed within 6 hours (1.8% versus 7.1%, P =0.041). Survival of STEMI and non‐STEMI patients was 94% versus 88% after 1 year ( P <0.001), 87% versus 73% after 5 years ( P <0.001), and 74% versus 57% after 10 years ( P <0.001). Independent predictors of 30‐day and long‐term mortality included preoperatively increased lactate values, age, atrial fibrillation, and reduced left ventricular function. Conclusions: Stable STEMI patients showed a lower rate of perioperative complications and better survival compared with non‐STEMI patients when CABG was performed within 48 hours.